Forest Products Collection of Hill Kharias of Mayurbhanj of Odishain Eastern India: A Recent Study - Tudu, Fagu; Mohapatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
This article is intended to analyze forest resources collected by the Hill Kharias of Odisha in Eastern India. The forest products of the Hill Kharias of Mayurbhanj have a unique retail characteristic, which is overlooked by most of the earlier scholars. In order to investigate the forest resources of the Hill Kharia people, the concept of the design in minor forest resources collection by them is masked by the development in their society in the modern period. The Hill Kharias trace their origin to a peafowl’s egg, and earlier scholars like Russell and Hiralal have mentioned they have been derived from Kharkharia, which means a palanquin or litter. So that they were called Kharia and lived in the forest area and seasonally collected a variety of forest-type resources like Mohu (honey), Patra (leaves), Katha (firewood), Fola (fruits), Chera (root, tuber), Chhatu (mushroom), etc. The groups of Aboriginals who constitute simple and small-scale societies were culturally homogeneous, had lifestyles isolated and inaccessible in tracts of hill and forest, and continue an archaic way of life and absorb the change slowly and are known as Particular Vulnerable Tribal Groups (PVTGs). The collection of forest products of Hill Kharias is one of the important aspects of their economic subsistence. Hence it is very interesting for scholars of tribal history to know about the details of the collection of forest production of people of the Hill Kharia tribe of Mayurbhanj. Further, it is also curious to identify the indigenous wisdom of the minor forest resources to understand the material culture of the Hill Kharia tribe of Mayurbhanj. The present article attempts to highlight the socioeconomic subsistence of Hill Kharias of Mayurbhanj based on their forest productions in detail.